PERAN KOPERASI SIMPAN PINJAM DANA NIAGA SYARIAH DALAM PEMBERDAYAAN EKONOMI MASYARAKAT SEBAGAI ALTERNATIF UNTUK MENGURANGI TINGKAT KEMISKINAN DI DESA LEMPANGAN KECAMATAN BAJENG KABUPATEN GOWA - Annisa, Nurul; Naidah, Naidah; Rasulong, Ismail (Universitas Muhammadiyah Makassar, 2020)
His study aims to determine the Role of Syariah Niaga Savings and Loan Cooperatives in Community Economic Empowerment as an Alternative to Reducing Poverty Rate in Lempangan Village, Bajeng District, Gowa Regency.This study used eight informants in Lempangan Village, Bajeng District, Gowa Regency. The eight authors' informants were all chairpersons and members of the Lempangan Village, Bajeng District, Gowa Regency. While the data analysis used is descriptive qualitative data analysis.The results showed that the Role of Syariah Savings and Loan Cooperative Cooperatives in Community Economic Empowerment as an Alternative to Reducing Poverty Rate in Lempangan Village, Bajeng District, Gowa Regency.